Posterolateral structure reconstruction for the chronic multiple ligament injuries of the knee - Kondo, Eiji; Joutoku, Zenta; Matsubara, Shinji; Iwasaki, Koji; Onodera, Tomohiro; Yasuda, Kazunori; Yagi, Tomonori; Iwasaki, Norimasa (Annals of Joint; Vol 4 (November 2019): Annals of Joint, 2019)
Combined anterior cruciate ligament (ACL) and posterior cruciate ligament (PCL) injuries results in severe functional knee disability. The posterolateral structure (PLS) injuries are commonly associated with PCL and/or ACL injuries by traffic accident or high energy trauma. The PCL is the primary restraint structure to posterior tibial translation of the knee. The PLS injury promote the functional disability of the PCL insufficiency. However, the treatment strategy for combined ligamentous injuries of the knee with the PLS insufficiency remains controversial. The authors have been performed PLS reconstruction using an autogenous biceps femoris tendon (BFT) for the chronic posterolateral (PL) instability of the knee. In this article, the surgical technique, and clinical outcomes of PLS reconstruction for the chronic PLS insufficiency with PCL and/or ACL ruptures.